Odpowiedzi

2010-04-16T20:52:36+02:00
A)BaCl2 + Na2CO3 ---> 2NaCl + BaCO3
Ba(2+) + 2Cl(-) + 2Na(+) + CO3(-2) --> 2Na(+) + Cl(2-) + BaCO3 ↓
Ba(2+) + CO3(-2) ---> BaCO3

b)Na2SiO3+ 4 HCl = 2 NaCl+ H2SiO3
2Na(+) + SiO3(-2) + 2H(+) + 2Cl(-) --> 2Na(+) +2Cl(-) + H2SiO3↓
2H(+) + SiO3(-2) --> H2SiO3

c) Pb(NO3)2 + K2S = 2KNO3 + PbS↓
Pb(+2) + 2NO3(-) + 2K(+)+ S(-2) =2K(+) + 2NO3(-) + PbS ↓
Pb(+2) + S(2-) = PbS↓

d) FeCl3 + 3NaOH → 3NaCl + Fe(OH)3↓
Fe(+3) + 3Cl(-) + 3Na(+) + 3 OH(-) --> 3 Na(+) + 3Cl(-) + Fe(OH)3↓
Fe(+3) + 3OH(-) --> Fe(OH)3↓


tO CO JEST W NAWIAZACH TO JONOWO TE LICZBY SA U GORY . mYSLE ZE BEDZIESZ WIEDZIEC O CO CHODZI :)